Analisis Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Berbasis Proyek di Sekolah Dasar - Rahayu, Suwasti; Markhamah, Markhamah; Fathoni, Achmad (Universitas Pendidikan Indonesia, 2025)
Project-based learning (PJBL) is a potential approach to develop critical thinking skills of elementary school students. This study aims to review and analyze the effectiveness of project-based learning in improving students' critical thinking skills. The research was conducted using the Systematic Literature Review (SLR) method, which was conducted by analyzing 15 empirical studies that met the inclusion criteria. The results show that project-based learning is significantly able to improve students' critical thinking skills, with the dominant aspects being the ability to analyze, evaluate, and conclude. Factors such as project characteristics, teacher role and group dynamics influence the effectiveness of project-based learning. The conclusion of this study is that project-based learning is proven to be effective in developing elementary school students' critical thinking skills. The findings provide a strong basis for implementing project-based learning as a strategy to develop critical thinking skills in elementary schools.